1993
DOI: 10.1152/jappl.1993.74.2.868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motor unit losses on strength in older men and women

Abstract: The influence of age-associated motor unit loss on contractile strength was investigated in a representative sample of healthy, active young and older men and women. In 24 younger subjects (22-38 yr) and 20 older subjects (60-81 yr) spike-triggered averaging was employed to extract a sample of surface-recorded single motor unit action potentials (S-MUAPs) from the biceps brachii and brachialis muscles. The amplitude of the maximum compound muscle action potential of the biceps brachii and brachialis muscles wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
232
2
11

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(266 citation statements)
references
References 0 publications
21
232
2
11
Order By: Relevance
“…One study, using decomposition-enhanced STA showed that Bvery elderly The ALS functional rating scale-revised (ALSFRS-R) is a global measure. HHD = hand-held dynamometry; MUNIX = Motor Unit Number Index; MIM = multipoint incremental *The coefficient of variation/correlation coefficient is not standard across the methods †Test-retest variability in normal subjects men^(mean age > 80 years) had even greater motor unit loss than Bolder men^(mean age 66 years) [107]. Motor unit loss associated with aging is a significant factor leading to agerelated reductions in muscle mass, strength, and power (often referred to as Bsarcopenia^).…”
Section: Mune In Other Neuromuscular Diseases and Normal Agingmentioning
confidence: 99%
“…One study, using decomposition-enhanced STA showed that Bvery elderly The ALS functional rating scale-revised (ALSFRS-R) is a global measure. HHD = hand-held dynamometry; MUNIX = Motor Unit Number Index; MIM = multipoint incremental *The coefficient of variation/correlation coefficient is not standard across the methods †Test-retest variability in normal subjects men^(mean age > 80 years) had even greater motor unit loss than Bolder men^(mean age 66 years) [107]. Motor unit loss associated with aging is a significant factor leading to agerelated reductions in muscle mass, strength, and power (often referred to as Bsarcopenia^).…”
Section: Mune In Other Neuromuscular Diseases and Normal Agingmentioning
confidence: 99%
“…Several groups have reported skeletal muscle denervation and re-innervation, motor unit remodelling or loss in aging rodents or humans (Hashizume et al ., 1988;Kanda & Hashizume, 1989, 1992Einsiedel & Luff, 1992;Doherty et al ., 1993;Johnson et al ., 1995;Zhang et al ., 1996). Motor unit remodelling leads to changes in fibre-type composition (Pette & Staron, 2001).…”
Section: Neural Influences On Aging Skeletal Musclementioning
confidence: 99%
“…Specifically, the plantar flexors have been identified as important loco-motor muscles that are important contributors to many functional-related activities in older adults such as walking speed (Clark et al 2013) and rising from a chair (Brown et al 1995). Furthermore, evidence suggests that distal muscles, such as the plantar flexors, may undergo relatively greater (compared to proximal muscles) age-related neurogenic adaptations (i.e., motor unit remodeling; Jennekens et al 1971), which have been suggested as being a primary contributor to the declines in force capacities observed across the life span (Doherty et al 1993). Given that plantar flexor neuromuscular function may be an important factor in overall performance and mobility in the elderly (Clark et al 2013), it would be expected that the adverse effects of aging on the plantar flexors may substantially contribute to the functional and lifestyle deficiencies commonly observed in the elderly.…”
Section: Introductionmentioning
confidence: 99%